A bucket of blood - Corman, Roger, 1926-; Griffith, Charles B.; primer actor mencionado en 511; segundo actor mencionado en 511; tercer actor mencionado en 511; del 264 1 $b; Cinetel Films ([Los Angeles, CA] : Alta Vista Productions, 1959)
A frustrated and talentless artist finds acclaim for a plaster covered dead cat that is mistaken as a skillful statuette. Soon the desire for more praise leads to an increasingly deadly series of works. --
Originally released as motion picture in 1959 and distributed by American International Pictures.
Movie distributed by Cinetel for Digitalia Film Library.
Dick Miller, Barboura Morris, Antony Carbone, Julian Burton.
Cinematographer, Jack Marquette; editor, Anthony Carras; music, Jerry Irvin.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 31, 2015)
Keywords: Serial murderers -- Drama; Sculptors -- Corrupt practices -- Drama; Beat generation -- Drama; Coffeehouses -- Drama; Venice (Los Angeles, Calif.); Los Angeles (Calif.); Horror films; Feature films; Internet videos; Streaming video